PREVALENCE AND STATISTICAL ANALYSIS OF HYMENOLEPIDOSIS IN THE PROVINCES OF THE REPUBLIC OF UZBEKISTAN (World Bulletin of Public Health, 2022)
Hymenolepidosis - Small worm (Hymeno-lepis nana) is 30-50 mm long (often 15-20 mm). The body is white-gray, thin, and consists of small joints that quickly decompose. Infection occurs mainly through contaminated care items (beds, chairs, doorknobs, toys) during contact with the patient
Keywords: Hymenolepidosis; occurs; items